DEPP/DEPP1/C10ORF10 regulates hepatic glucose and fat metabolism partly via ROS‐induced FGF21. Issue 10 (27th April 2018) - Li, Wenli; Ji, Meiling; Lin, Yandie; Miao, Yi; Chen, Simin; Li, Hao
ABSTRACT: Decidual protein induced by progesterone (DEPP/DEPP1/C10ORF10) is induced by denying access to food and reduced by refeeding in insulin‐sensitive organs in vivo. The negative regulation of DEPP by insulin is also proven in several cell lines. However, the functions of DEPP in insulin‐sensitive organs remain unknown. In the present study, we investigated the impact of DEPP on hepatic energy metabolism and addressed the underlying mechanisms. The metabolic effects of DEPP were investigated in mice with adenovirus‐mediated hepatic overexpression. Liver triglyceride (TG), glycogen, and serum metabolites were detected by biochemical assays. Energy homeostasis was measured by indirect calorimetry. Quantitative PCR was used to examine expression of genes involved in fatty acid oxidation, ketogenesis, lipogenesis, and gluconeogenesis. To evaluate the role of fibroblast growth factor 21 (FGF21) mediating the metabolic effects of DEPP, FGF21 antibody was administrated intraperitoneally to mice at 24 h after the delivery of adenovirus, and the metabolic alterations were examined. Reactive oxygen species (ROS) levels were measured by catalase activity assay, live cell fluorescence, or quantitative PCR. Effects of DEPP on the phenotype of db/db mice were also assessed. Acute hepatic overexpression of DEPP significantly reduced serum glucose and TG levels, dramatically elevated β‐hydroxybutyrate levels, and improved glucose clearance. Compared with controls, DEPP overexpression reduced food intake, the energy expenditure rate, and the respiratory quotient. DEPP overexpression significantly increased fatty acid oxidation and ketogenesis but suppressed lipid synthesis and gluco‐ neogenesis. Investigations of the underlying mechanisms revealed that DEPP regulates energy metabolism by inducing oxidative stress. With the impairment of the ROS scavenging system and promotion of ROS formation, DEPP overexpression leads to ROS accumulation. FGF21 is upregulated in response to oxidative stress and mediates the effects of DEPP on fatty acid oxidation, ketogenesis, and lipid synthesis but not gluconeogenesis, as evidenced by the fact that the FGF21 antibody dramatically suppressed a DEPP‐induced increase of fatty acid oxidation and keto‐ genesis, reversed the reduction of lipid synthesis, but did not change the suppression of gluconeogenesis. Moreover, overexpression of DEPP in db/db mice led to a marked reduction in body weight and serum glucose levels and significantly improved insulin sensitivity. Hepatic overexpression of DEPP in mice promotes fatty acid oxidation and ketogenesis and suppresses lipogenesis and gluconeogenesis, which is partly mediated by FGF21 induced by elevated cellular ROS levels.—Li, W., Ji, M., Lin, Y., Miao, Y., Chen, S., Li, H. DEPP/DEPP1/C10ORF10 regulates hepatic glucose and fat metabolism partly via ROS‐induced FGF21. FASEB J. 32, 5459–5469 (2018). www.fasebj.org